Alterations in Protein Regulators of Neurodevelopment in the Cerebrospinal Fluid of Infants with Posthemorrhagic Hydrocephalus of Prematurity - Morales, Diego M. (The American Society for Biochemistry and Molecular Biology, 2012)
Neurological outcomes of preterm infants with posthemorrhagic hydrocephalus are among the worst in newborn medicine. There remains no consensus regarding the diagnosis or treatment of posthemorrhagic hydrocephalus, and the pathological pathways leading to the adverse neurological sequelae are poorly understood. In the current study, we developed an innovative approach to simultaneously identify potential diagnostic markers of posthemorrhagic hydrocephalus and investigate novel pathways of posthemorrhagic hydrocephalus-related neurological disability. Tandem multi-affinity fractionation for specific removal of plasma proteins from the hemorrhagic cerebrospinal fluid samples was combined with high resolution label-free quantitative proteomics. Analysis of cerebrospinal fluid obtained from infants with posthemorrhagic hydrocephalus demonstrated marked differences in the levels of 438 proteins when compared with cerebrospinal fluid from age-matched control infants. Amyloid precursor protein, neural cell adhesion molecule-L1, neural cell adhesion molecule-1, brevican and other proteins with important roles in neurodevelopment showed profound elevations in posthemorrhagic hydrocephalus cerebrospinal fluid compared with control. Initiation of neurosurgical treatment of posthemorrhagic hydrocephalus resulted in resolution of these elevations. The results from this foundational study demonstrate the significant promise of tandem multi-affinity fractionation-proteomics in the identification and quantitation of protein mediators of neurodevelopment and neurological injury. More specifically, our results suggest that cerebrospinal fluid levels of proteins such as amyloid precursor protein or neural cell adhesion molecule-L1 should be investigated as potential diagnostic markers of posthemorrhagic hydrocephalus. Notably, dysregulation of the levels these and other proteins may directly affect ongoing neurodevelopmental processes in these preterm infants, providing an entirely new hypothesis for the developmental disability associated with posthemorrhagic hydrocephalus.